Molecular Mechanisms and Therapeutic Targeting of Heat Shock Proteins (HSPs) in Cardiovascular Disorders - Jyoti Upadhyay; Mukesh Nandave; Kamal Y. Thajudeen; Summya Rashid; Mohd Nazam Ansari (Frontiers in Bioscience-Landmark)
Identifying novel biomarkers is a reliable approach to predict and diagnose human diseases as well as manage individual responses to therapeutic drugs. Heat shock proteins (HSPs) are molecular chaperones that play a major role in maintaining protein stability and folding. Many studies suggested their association with multiple types of diseases. HSPs from different categories play different roles; therefore, it is important to identify HSPs and their function to understand their biological functions clearly. This comprehensive review was performed to evaluate the role of HSPs as predictive biomarkers in cardiovascular diseases. The original publications related to HSPs from 2010 to 2024 were identified by using the keywords “heat-shock proteins”, “HSP in cardiovascular disorders” and “HSP in atherosclerosis”. The regulatory pathways involved in HSPs’ functioning are the important points of discussion in this review. HSPs play a critical role in key cellular processes, including apoptosis regulation, protein folding, immune responses, genomic stability, and DNA repair. Aberrant expression of HSPs causes dysregulation of these pathways resulting in the development and progression of diseases. A comprehensive understanding of HSPs in cardiovascular diseases and their associated regulatory pathways can have significant implications for disease intervention, diagnosis, and prognosis. In this review paper, we have highlighted the importance of HSPs as versatile biomarkers and their importance as targets for the therapeutic management of cardiovascular diseases.